Sex and gender factors affecting metabolic homeostasis, diabetes and obesity - Mauvais-Jarvis, Franck, 1965- (Springer, 2017)
The book provides a reference for years to come, written by world-renowned expert investigators studying sex differences, the role of sex hormones, the systems biology of sex, and the genetic contribution of sex chromosomes to metabolic homeostasis and diseases. In this volume, leaders of the pharmaceutical industry present their views on sex-specific drug discovery. Many of the authors presented at the Keystone Symposium on "Sex and gender factors affecting metabolic homeostasis, diabetes and obesity" to be held in March 2017 in Lake Tahoe, CA. This book will generate new knowledge and ideas on the importance of gender biology and medicine from a molecular standpoint to the population level and to provide the methods to study them. It is intended to be a catalyst leading to gender-specific treatments of metabolic diseases. There are fundamental aspects of metabolic homeostasis that are regulated differently in males and females, and influence both the development of diabetes and obesity and the response to pharmacological intervention. Still, most preclinical researchers avoid studying female rodents due to the added complexity of research plans. The consequence is a generation of data that risks being relevant to only half of the population. This is a timely moment to publish a book on sex differences in diseases as NIH leadership has asked scientists to consider sex as a biological variable in preclinical research, to ensure that women get the same benefit of medical research as men.
Keywords: Sex factors in disease.; elektronické knihy; electronic books